Copper-Catalyzed N -Arylation of Sulfoximines with Arylboronic Acids under Mild Conditions - Gupta S.; Baranwal S.; Muniyappan N.; Sabiah S.; Kandasamy J. (My University, 2025)
N -Arylation of sulfoximines with different arylboronic acids, including sterically hindered boronic acids, is achieved using copper(I) iodide and 4-DMAP at room temperature. Moreover, N -arylation of biologically relevant l -methionine sulfoximine is demonstrated for the first time. All these reactions provided the desired products in excellent yields within a short span of time. The optimized reaction conditions are well suited to the task of N -vinylation of sulfoximine with trans -2-phenylvinylboronic acid. © Georg Thieme Verlag Stuttgart New York.